1993
DOI: 10.1017/s1742758400018178
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics and host range of Macrotoma palmata F. (Coleoptera: Cerambycidae)

Abstract: In Egypt, Macrotomapalmata F. (Coleoptera: Cerambycidae) is a serious polyphagous pest attacking fruit, wood and ornamental trees. Apricot orchards, however, are liable to severe infestation especially in dense plantations. Hosts and degree of infestation in Matrouh, Alexandria, Fayoum and North Sinai were recorded. The seasonal fluctuation in population was monitored on apricot trees at Alexandria and Giza governorates throughout the 3 successive years (1987)(1988)(1989). M. palmata started to emerge during J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Larvae of C. varius feed inside the stem and main branches of trees and cause their death, and the total life cycle was completed in almost one year (Tadros, 1993). Frequent field observations indicated that the most important boring pests in citrus orchards are the Coleopterous Cerambycids C. varius that attack 21 fruit tree species (Tadros, 1994) and 14 wood and ornamental tree species (Nour, 1963 andHaggag, 1982), Macrotoma palmata also attack citrus trees (Tadros et al, 1993), the Scolytids Hypothenemus eruditus seriously infest sweet lemon, mandarin, lemon and kumquat (Batt et al, 1993), Scolytus amygdale (Tadros, 1994) and the Bostrichid Enneadesmus obtusedentatus (Tadros et al, 1997), as well as the Lepidopterous Cossid Paropta paradoxa was recorded attacking mandarin trees (El-Assal et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Larvae of C. varius feed inside the stem and main branches of trees and cause their death, and the total life cycle was completed in almost one year (Tadros, 1993). Frequent field observations indicated that the most important boring pests in citrus orchards are the Coleopterous Cerambycids C. varius that attack 21 fruit tree species (Tadros, 1994) and 14 wood and ornamental tree species (Nour, 1963 andHaggag, 1982), Macrotoma palmata also attack citrus trees (Tadros et al, 1993), the Scolytids Hypothenemus eruditus seriously infest sweet lemon, mandarin, lemon and kumquat (Batt et al, 1993), Scolytus amygdale (Tadros, 1994) and the Bostrichid Enneadesmus obtusedentatus (Tadros et al, 1997), as well as the Lepidopterous Cossid Paropta paradoxa was recorded attacking mandarin trees (El-Assal et al, 2008).…”
Section: Introductionmentioning
confidence: 99%